United we stand, divided we fall: developing an integrated collaborative teaching model for hospitality online education - Ngelambong, Anderson; Siao, Fui Wong; Choirisa, Septi Fahmi; Jasrotia, Aruditya; Abdul Hadi, Arnieyantie (GADING (Online) Journal for Social Sciences, 2024)
Collaborative teaching, known as co-teaching, has garnered popularity in recent years due to its ability to enhance learning outcomes. Albeit its advantages, collaborative teaching is challenged by the complexity of management and implementation. Numerous scholars have attempted to propose co-teaching methods and strategies to resolve the issue. A conceptual framework in collaborative teaching still needs to be discovered, particularly one that connects various stakeholders from domestic and international levels. To fill the gap, this study conceptualised an Integrated Collaborative Teaching Model for hospitality education. Guided by social learning theory and constructivism, the conceptual framework proposes online teaching delivery via various methods (e.g., Blended Learning, Asynchronous Learning, Synchronous Learning, Virtual Field Trips) by academic experts, industry practitioners, and policy developers from local, regional, and international levels. The study aligns with Sustainable Development Goal 4, which is to alleviate the quality of education. The findings are expected to improve the existing curriculum, enhance the teaching and learning experience, and promote lifelong learning opportunities. The study recommends that more studies be conducted to test the integrated collaborative teaching framework empirically.